Transcriptomic links to muscle mass loss and declines in cumulative muscle protein synthesis during short‐term disuse in healthy younger humans. Issue 9 (3rd August 2021) - Willis, Craig R. G.; Gallagher, Iain J.; Wilkinson, Daniel J.; Brook, Matthew S.; Bass, Joseph J.; Phillips, Bethan E.; Smith, Kenneth; Etheridge, Timothy; Stokes, Tanner; McGlory, Chris; Gorissen, Stefan H. M.; Szewczyk, Nathaniel J.; et al.
Abstract: Muscle disuse leads to a rapid decline in muscle mass, with reduced muscle protein synthesis (MPS) considered the primary physiological mechanism. Here, we employed a systems biology approach to uncover molecular networks and key molecular candidates that quantitatively link to the degree of muscle atrophy and/or extent of decline in MPS during short‐term disuse in humans. After consuming a bolus dose of deuterium oxide (D2 O; 3 mL.kg −1 ), eight healthy males (22 ± 2 years) underwent 4 days of unilateral lower‐limb immobilization. Bilateral muscle biopsies were obtained post‐intervention for RNA sequencing and D2 O‐derived measurement of MPS, with thigh lean mass quantified using dual‐energy X‐ray absorptiometry. Application of weighted gene co‐expression network analysis identified 15 distinct gene clusters ("modules") with an expression profile regulated by disuse and/or quantitatively connected to disuse‐induced muscle mass or MPS changes. Module scans for candidate targets established an experimentally tractable set of candidate regulatory molecules (242 hub genes, 31 transcriptional regulators) associated with disuse‐induced maladaptation, many themselves potently tied to disuse‐induced reductions in muscle mass and/or MPS and, therefore, strong physiologically relevant candidates. Notably, we implicate a putative role for muscle protein breakdown‐related molecular networks in impairing MPS during short‐term disuse, and further establish DEPTOR (a potent mTOR inhibitor) as a critical mechanistic candidate of disuse driven MPS suppression in humans. Overall, these findings offer a strong benchmark for accelerating mechanistic understanding of short‐term muscle disuse atrophy that may help expedite development of therapeutic interventions.